The Effect of Financial Literacy and Financial Inclusion on the Financial Performance of MSMEs in the City of Bandung - Rieke Sri Rizki Asti Karini; Panji Pamungkas (Riwayat: Educational Journal of History and Humanities, 2025)
This study examines the level of understanding and use of financial institution products in MSME actors in the city of Bandung which is a solution to the problem of making decisions in order to achieve success in financial performance, namely company profits. The aim is to determine the influence of financial literacy and financial inclusion on financial performance in MSMEs in the city of Bandung. Using the purposive sampling method with a survey approach. Data collection uses a questionnaire distributed through a google form to MSMEs in the city of Bandung. The analysis tool used is multiple Linear Regression.